2014
DOI: 10.1021/jo4028006
|View full text |Cite
|
Sign up to set email alerts
|

Cycloisomerization of Acetylenic Acids to γ-Alkylidene Lactones using a Palladium(II) Catalyst Supported on Amino-Functionalized Siliceous Mesocellular Foam

Abstract: Cycloisomerization of various γ-acetylenic acids to their corresponding γ-alkylidene lactones by the use of a heterogeneous Pd(II) catalyst supported on amino-functionalized siliceous mesocellular foam is described. Substrates containing terminal as well as internal alkynes were cyclized in high to excellent yields within 2-24 h under mild reaction conditions. The procotol exhibited high regio-and stereoselectivity, favoring the exo-dig product with high (Z)-selectivity. Moreover, the catalyst displayed excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…Interestingly, the Pd II ‐precursor of this Pd 0 nanocatalyst, can also be used as a catalyst for a number of useful reactions. For example, this Pd II ‐AmP‐MCF catalyst has been employed for the cycloisomerization of alkynoic acids and for the oxidative carbocyclization–borylation of enallenols . Additionally, this Pd II ‐AmP‐MCF could be utilized as a catalyst in the chemodivergent syntheses of γ‐lactones and γ‐lactams by different oxidative tandem processes …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the Pd II ‐precursor of this Pd 0 nanocatalyst, can also be used as a catalyst for a number of useful reactions. For example, this Pd II ‐AmP‐MCF catalyst has been employed for the cycloisomerization of alkynoic acids and for the oxidative carbocyclization–borylation of enallenols . Additionally, this Pd II ‐AmP‐MCF could be utilized as a catalyst in the chemodivergent syntheses of γ‐lactones and γ‐lactams by different oxidative tandem processes …”
Section: Methodsmentioning
confidence: 99%
“…When using either Pd 0 ‐AmP‐MCF or commercial Pd/C as catalysts in the model reaction, significantly lower yields of product 2 a was obtained compared to the corresponding reaction with the Pd II ‐AmP‐MCF catalyst. In a previous study we had observed that additions of BQ to the Pd II ‐AmP‐MCF catalyst gave a highly active catalyst with surface‐confined Pd II species; however, this approach did not lead to any improvements in the present cycloisomerization reaction with the Pd II ‐AmP‐MCF.…”
Section: Methodsmentioning
confidence: 99%
“…Owing to the great importance of these intriguing structures, much attention was paid to exploring synthetic methods, and tremendous progress have been achieved over the last decades. Many synthetic methodologies were well established to prepare lactones, such as oxidative cyclization reaction of alkynylbenzaldehydes catalyzed by NHC (N‐heterocyclic carbenes), bromolactonization of long‐chain olefinic acids promoted by sulfur‐based zwitterionic organocatalyst, intermolecular [6+2] cyclization of amphoteric molecules with siloxy alkynes, oxetene ring‐opening reaction, borylated lactones from esters with electrophilic oxyboration, and intramolecular addition of carboxylic acids or esters to alkynes or alkenes promoted by transition metal, organic acids or bases . Among these synthetic routes to lactones, the cycloisomerization of alkynoic acids is a straightforward and attractive synthetic method to access lactones with great atom economy .…”
Section: Figurementioning
confidence: 99%
“…Among these synthetic routes to lactones, the cycloisomerization of alkynoic acids is a straightforward and attractive synthetic method to access lactones with great atom economy . These cycloisomerization reactions have been extensively investigated by Pd, Rh, Ru, Pt and Au catalytic systems. And they were mainly focused on the preparation of five‐ and six‐membered lactones, the synthesis of seven‐membered lactones is very challenging and less studied, which were always listed as one to three examples with poor to moderate yields.…”
Section: Figurementioning
confidence: 99%
“…[8] This catalyst has been found to effectively catalyze aw ide range of transformations, exhibiting high recyclability and low metal leaching. [10] Herein, we report our results on nanopalladium-catalyzed synthesis of benzofurans and indoles and provide furtherc haracterizationo fb otht he Pd II pre-catalyst and the Pd 0 -AmP-MCF catalyst with the aid of extended X-ray absorption fine-structures pectroscopy (EXAFS). [10] Herein, we report our results on nanopalladium-catalyzed synthesis of benzofurans and indoles and provide furtherc haracterizationo fb otht he Pd II pre-catalyst and the Pd 0 -AmP-MCF catalyst with the aid of extended X-ray absorption fine-structures pectroscopy (EXAFS).…”
Section: Introductionmentioning
confidence: 97%